2018
DOI: 10.1097/gox.0000000000001844
|View full text |Cite
|
Sign up to set email alerts
|

Photometric Evaluation of Long-term Changes in Breast Shape after Breast Augmentation and Vertical Mammaplasty

Abstract: Background:Little information is presently available regarding the long-term effects of breast augmentation and mammaplasties on breast shape. Existing studies typically use 1-dimensional measurements and mean follow-up times seldom exceed 1 year.Methods:Twenty women were studied: breast augmentation (n = 5), mastopexy (n = 5), augmentation/mastopexy (n = 5), and breast reduction (n = 5). For mammaplasties, a vertical method using a medial pedicle and intraoperative nipple siting was used in all cases. A 2-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“… 40 , 106 Central mound techniques require skin undermining, increasing the risk of delayed wound healing. 9 Measurement changes are similar to those produced by implants alone 14 , 107 109 (Fig. 3 ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“… 40 , 106 Central mound techniques require skin undermining, increasing the risk of delayed wound healing. 9 Measurement changes are similar to those produced by implants alone 14 , 107 109 (Fig. 3 ).…”
Section: Discussionsupporting
confidence: 71%
“…Nipple overelevation may be avoided. 19 , 107 , 109 Vertical mammaplasty requires less operating time than the Wise pattern and offers a high degree of safety because the superficial pedicle (wholly located anterior to the breast implant rather than tethered at the inframammary fold) is short and robust. 106 , 110 A medial or superomedial dermal connection is preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, morphological changes due to aging have not been accounted for. Fortunately, morphological changes up to 10 years after augmentation remain small and validates the use of this comparative cohort of cis women [29]. Despite these limitations, this study found highly distinctive characteristics in breast anthropometry between trans and cis women, and is the first study to have compared these outcomes in such detail.…”
Section: Discussionmentioning
confidence: 51%
“…Methods include simple tape measure-based systems such as described here, [4][5][6][7] measurements taken from standardized photographic images [8][9][10][11] and 3-dimensional scanning systems. [12][13][14][15][16] Although it has been suggested that direct measurements lead to considerable interobserver and intraobserver error, this is not the case.…”
Section: Discussionmentioning
confidence: 99%